Web Event, Spring Boot, Java Pembangunan Aplikasi Web Event menggunakan Framework Spring Boot di PT XYZ - Willyam Chrisna Umbu Dagha (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
XYZ is a company engaged in the development of information technology. In addition to engaging in the development of information technology PT. XYZ is also actively engaged in providing education to students, lecturers and the public in the form of learning events held by PT. XYZ. After the passage of time, several problems arise, because registration through online registration form causes the registrant must fill in complete data repeatedly if participating in different events and information about the event is very limited because it is only socialized through Instagram. This creates inconvenience on the registrant's side, so that it can reduce enthusiastic event registration. This study aims to build applications in the form of a web application that aims to manage complete event information and facilitate the applicants to register. This system was developed using the Spring Boot Framework with the Java programming language. Spring Boot greatly facilitate the development of the system because it is open source, complete documentation, and complete modules such as JDBC, ORM, Servlet, etc. Spring Boot itself supports the creation of applications based on restfull web service so that it allows programmers to combine it with other programming languages. The result of this research is a web event application.